2009
DOI: 10.1101/gr.092114.109
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide mapping of SMAD target genes reveals the role of BMP signaling in embryonic stem cell fate determination

Abstract: Embryonic stem (ES) cells are under precise control of both intrinsic self-renewal gene regulatory network and extrinsic growth factor-triggered signaling cascades. How external signaling pathways connect to core self-renewal transcriptional circuits is largely unknown. To probe this, we chose BMP signaling, which is previously recognized as a master control for both self-renewal and lineage commitment of murine ES cells. Here, we mapped target gene promoter occupancy of SMAD1/5 and SMAD4 on a genome-wide scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
118
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 55 publications
8
118
0
1
Order By: Relevance
“…Accordingly, sequence analysis of the genomic region upstream the miR-cluster identified many consensus binding sites for Smads. 4 These data indicated that transcription of the miR-23a cluster gene is regulated by BMP4.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Accordingly, sequence analysis of the genomic region upstream the miR-cluster identified many consensus binding sites for Smads. 4 These data indicated that transcription of the miR-23a cluster gene is regulated by BMP4.…”
mentioning
confidence: 94%
“…3 This effect is mediated by the regulation of many direct targets of Smad1, 5 and 8, the transcription factors downstream of the BMP4 receptor. 4 BMP4 also contributes to govern early steps of differentiation. First, BMP4 acts by regulating ESC-epiblast transition and then by suppressing neural differentiation and promoting non-neural lineage formation.…”
mentioning
confidence: 99%
“…To obtain a more precise picture of the roles of Smad2-mediated Activin/Nodal signaling in mouse ES cell differentiation, we adopted a more direct differentiation system, in which ES cells were cultured as monolayer in a defined N2B27-supplemented medium without feeder, serum or serum replacement [21]. The cells were differentiated toward mesendoderm with Activin treatment for 4-5 days; otherwise the cells underwent neuroectoderm differentiation in the absence of Activin (data not shown).…”
Section: Smad2-mediated Activin/nodal Signaling Regulates Distinct Famentioning
confidence: 99%
“…Genomic DNA immunoprecipitated by Smad2 was then amplified, labeled with fluorophores and finally detected on the Agilent mouse promoter arrays, consisting of ~60-base pair (bp) probes at ~200-bp intervals covering from upstream −5.5 kilobases (kb) to downstream +2.5 kb promoter regions relative to the transcriptional start sites (TSS) for ~17 000 annotated genes of the mouse genome. Binding sites were defined by the method described previously [21], which was shown to obtain a highly credible data set with a falsepositive rate of less than 20% as validated by ChIP-PCR and other criteria. Seven hundred ninety-two genes harboring Smad2 binding sites were identified (Supplementary information, Table S1).…”
Section: Genome-wide Identification Of Smad2-bound Genes In Es Cellsmentioning
confidence: 99%
See 1 more Smart Citation